Analysis of the Effect of Work Placement Suitability on Employee Work Performance in the Tarutung Road and Bridge Technical Implementation Unit of the Bina Marga and Construction Service of North Sumatra Province - Santoris Panjaitan; Delviana RW. Sihombing (Jurnal Mantik, 2021)
Employee work performance can be maximally achieved if the organization is willing to pay attention and develop the abilities and mindset and behavior of employees. The proper placement of employees is a way to optimize knowledge, skills and attitudes towards optimal work performance. Hasibuan (2001: 71) argues that proper employee placement is one of the keys to obtaining optimal work performance from each employee. Types and sources of data used are primary data, which are data obtained from competent parties, in this case the Tarutung Road and Bridge Technical Implementation Unit staff, the Office of Bina Marga and Construction, North Sumatra Province and secondary data are data obtained by the author from data that has been published in the form of books or magazines. The data obtained from the questionnaire distributed to a sample of 20 people shows that the value of the relationship or influence of job placement suitability on employee job performance through statistical testing is 0.706 categorized in the strong category level. The coefficient of determination from these data is 49.9% and the remaining 50.1% is influenced by other factors. The results of the regression calculation Y = 10,282 + 0,280 X in the sense that if the value of Job Placement Conformity increases by 1, the increase in employee job performance increases by 0.280. The results of hypothesis testing are known through the t test, which is equal to the value of tcount> ttable, namely 4.231> 1.734.